2000
DOI: 10.1152/ajplung.2000.278.6.l1107
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase C-α mediates endothelial barrier dysfunction induced by TNF-α

Abstract: We tested the hypothesis that protein kinase C-alpha (PKC-alpha) mediates tumor necrosis factor-alpha (TNF-alpha)-induced alterations in permeability of pulmonary microvessel endothelial monolayers (PEM). The permeability of PEM was assessed by the clearance rate of Evans blue-labeled albumin. PEM lysates were analyzed for PKC-alpha mRNA (Northern cDNA blot), protein (Western immunoblot), and activity (translocation and phosphorylation of myristoylated arginine-rich C kinase substrate). Incubation of PEM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 42 publications
10
87
0
1
Order By: Relevance
“…It is significant that TNF synergizes with S1P in the control of epithelial permeability (35)(36)(37)(38) while also regulating pulmonary microvessel endothelium (38,39). TNF at higher concentrations leads to down-regulation of ZO-1 protein expression and disturbance in junctional localization of ZO-1 protein, and functional opening of the tight junction barrier (40).…”
Section: Discussionmentioning
confidence: 99%
“…It is significant that TNF synergizes with S1P in the control of epithelial permeability (35)(36)(37)(38) while also regulating pulmonary microvessel endothelium (38,39). TNF at higher concentrations leads to down-regulation of ZO-1 protein expression and disturbance in junctional localization of ZO-1 protein, and functional opening of the tight junction barrier (40).…”
Section: Discussionmentioning
confidence: 99%
“…PKC signaling is implicated in modulating barrier function both in endothelial cells containing tight junctions (Lippoldt et al, 2000;Sukumaran and Prasadarao, 2003), like those making up the blood-brain barrier, as well as those without tight junctions. PKC is a common downstream signaling pathway important in response to a number of endothelial cell permeability-inducing agents, including vascular endothelial growth factor (VEGF) (Wu et al, 1999;Breslin et al, 2003), thrombin (Lynch et al, 1990), TNF␣ (Ferro et al, 2000), bradykinin (Murray et al, 1991;Shigematsu et al, 2002), plateletactivating factor (Kobayashi et al, 1994), and reactive oxygen species (Zhao and Davis, 1998). PKC functioning downstream of VEGF activation has been shown to play a key role in both the mitogenic and permeability-inducing activities of VEGF (Wu et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This effect does not appear to be dependent on MEK1/2 and p38. To further assess the mechanism of increased response to PMA, we performed Western blots on RBE4 cell lysates to assess expression of PKC isoforms that are reported to be expressed in endothelial cells and that are stimulated by PMA (Ferro et al, 2000;Idris et al, 2001;SiflingerBirnboim and Johnson, 2003). No significant change in expression levels of PKC-␣, -␤, -␥, -␦, or -⑀ were detected between Verge expressing and nonexpressing RBE4 cell lines (Fig.…”
Section: Stable Verge-expressing Rbe4 Cells Show Increased Sensitivitmentioning
confidence: 99%
“…TNF-a-mediated endothelial barrier dysfunction was shown to be dependent on an increase in PKC-a activity. Furthermore, the antisense of PKC-a reduced the TNF-a-induced increase in endothelial permeability (120). Other studies have reported that VEGF can increase vascular permeability through activation of PKC-b in vivo and, importantly, oral administration of PKC b-isoformselective inhibitors partially inhibited VEGF-induced vascular permeability (4).…”
Section: Pkcsmentioning
confidence: 99%